Pengaruh Rasio Likuiditas, Leverage dan Profitabilitas Terhadap Return Saham Studi Empiris Pada Perusahaan Food and Bevarges - Rifani Akbar Sulbahri; Koefrowi Koefrowi; Sri Hartati (P3M STIE Mulia Darma Pratama, 2019)
In the Indonesia Stock Exchange (BEI), Food and Bevarges companies experience increases and decreases in returns. In the Indonesia Stock Exchange (BEI), Food and Bevarges companies experience an increase and decrease in stock returns. That was caused by internal and external factors of the company. The information contained in the company's financial statements, is a factor that comes from within the company. In this study aims to determine the effect of liquidity ratios, leverage and profitability on stock returns. This study uses Current Ratio (CR), Debt to Equity Ratio (DER), Return On Equity (ROE) as the independent variables. Hypothesis testing is done using the F test, t test, and R2. Hypothesis research results show that Current Ratio (CR), Dept to Equity Ratio (DER), Return On Equity (ROE) together have a significant effect on stock returns of Food and Beavages companies listed on the Indonesia Stock Exchange with a significance below 0.05 which is 0,000. From the research it is also known that partially the current ratio (CR) has no effect on the stock returns of Food and Bevarages companies listed in the Indonesian stock exchange, whereas Debt to Equity Ratio (DER), Return On Equity has an influence on the stock returns of Food and Bevarage companies that listed on the Indonesia Stock Exchange. The result of the calculation of the coefficient of determination R2 is 0.726, which means that the independent variables in this study together contribute to the dependent variable is 20.4% influenced by other variables not examined in this study. Suggestions For food and beverage companies, it is expected to pay more attention to the company's ability to increase stock returns through various ways, especially in the utilization of debt, utilization of current assets, utilization of capital to expand business and increase productivity to obtain high profits.